Establishing Initial Content Validity, Interrater Reliability, and Intra-rater Reliability of the Revised Visual Activity Sort for At-Risk Adolescents and Young Adults. - Gutman, Sharon; O'Day, Katie; Choi, Ashley; Kearney, Alexis; Rogers, Sandra (Open Journal of Occupational Therapy (OJOT))
Background: The purpose of this study was to establish the content validity and inter- and intra-rater reliability of the revised Visual Activity Sort, which is a card sorting assessment designed specifically for at-risk adolescents and young adults. Method: Six content experts were selected and asked to rate the relevancy of each of the 121 Visual Activity Sort cards. Two trained raters participated in the establishment of inter- and intra-rater reliability with 30 high school students attending a charter school for at-risk adolescents and young adults in a socioeconomically disadvantaged urban area. Results: Based on the content experts' ratings, a final summary content validity index of 74 maintained cards was established as high (CVI = 0.91, p < 0.05). Both inter- and intra-rater reliability were found to be high with ICCs of 0.83 and 0.84 (p < .000), respectively. Conclusion: Raters and authors recommended the addition of five cards addressing social media and internet safety, setting and maintaining healthy boundaries, managing social media and internet use and addiction, and navigating government agencies. These cards will be added and examined by content experts in a future study.